Generation of pulsed dual wavelength erbium doped fiber laser - Abdul Hadi, Fatin Shaqira (2019)
Single and dual wavelength fiber lasers and pulsed fiber lasers are well-known to be used for various applications. In the generation of dual wavelength fiber lasers and pulsed fiber lasers, the researchers found the mode competition among the dual wavelength is caused by the cross-gain saturation and strong homogeneous line broadening faced by erbium doped fiber (EDF). Therefore, the aim of this thesis is to generate a single and dual wavelength fiber laser and pulsed fiber laser by using fiber Bragg grating (FBG) in single ring and Figure-8 configurations at 1550 nm and 1560 nm. Analysis and optimization on single wavelength fiber laser and single wavelength pulsed fiber laser give a peak power of -10.70 dBm (8.51x10-2 mW) and -54.01 dBm (3.97x10-6 mW) with signal to noise ratio (SNR) of 59.70 dB and 10.29 dB, respectively, at 1550 nm. Similarly, at 1560 nm, this gives a peak power of -13.60 dBm (4.37x10-2 mW) and -60.00 dBm (1.00x10-6 mW) with SNR of 57.60 dB and 8.78 dB, respectively. For dual wavelength fiber laser and dual wavelength pulsed fiber laser, this gives a peak power of -12.90 dBm (5.13x10-2 mW) and -54.03 dBm (3.95x10-6 mW) at 1550 nm and a peak power of -14.80 dBm (3.24x10-2 mW) and -57.99 dBm (1.59x10-6 mW) at 1560 nm, respectively. The SNR obtained for 1550 nm and 1560 nm for dual wavelength fiber laser and dual wavelength pulsed fiber laser are 55.38 dB and 11.16 dB and 53.58 dB and 11.27 dB, respectively. The repetition rate of single and dual wavelength pulsed fiber laser is 2.878 MHz. It can be concluded that single and dual wavelength fiber lasers are successfully generated using single ring and figure-8 configurations whereas single and dual wavelength pulsed fiber laser are generated using only Figure-8 configuration due to mode locking occurrence. The polarization inside the cavity is controlled to solve mode competition and homogeneous in EDF, in order to obtain a stable dual wavelength.